Ethnic identity: A theoretical framework - Gil S. Epstein; Odelia Heizler (IZA Journal of Migration, 2015)
We present a basic theoretical framework of ethnic identity, i.e., the level of immigrant's commitment to his or her host society as well as the immigrant's commitment to his or her home society. Our model can explain the emerging empirical literature which studies the effect of the immigrants' characteristics, such as age, gender, education, religion, age at arrival, stock of immigrants in the host country, etc., on their ethnic identity (such as the Ethnosizer). In addition, this paper can be used as a basis for future empirical and theoretical research on this topic.
Keywords: F22; J15; Z13; 330; Ethnic identification; Ethnosizer; Immigrants; Assimilation; Integration; Separation; Marginalization